Problems in the implementation of economic reforms at the state level - Venkatesan, R. (New Delhi, 1994)
Industrial and trade licensing which had crippled the efficiency of the domestic industry all these years have been dismantled considerably. However for these reforms to be effective, the State level impediments should not become a constraint for implementation of the reforms programme. The book identifies and analyses the problems of implementation encoun tered or likely to be encountered at the State level especially for the expansion, modernisation and setting up of new units in the industrial sector and service enterprises. The study is confined to the industrial and services sectors, including small, medium and large scale industries; it also examines as to how specially because of measures taken by the State Government, these have benefitted from the reform and liberalisation policies adopted by the Central Government in the recent years.
Keywords: Economic reforms India States 1990